The final seven [large type] - Spindler, Erica, 1957- (Spindler, Erica, 1957- Lightkeepers, 2016)
"A new kind of evil is at work in the Crescent City, more cunning, more powerful than New Orleans Detective Micki Dee Dare has ever encountered. As another coed goes missing, Micki and her partner, Zach "Hollywood" Harris, an irreverent charmer fresh out of an experimental FBI program, may be the only ones who can stop it"--